Defining the flexicurity index in application to European countries - Andranik S. Tangian (Hans-Böckler-Stiftung, Wirtschafts- und Sozialwissenschaftliches Institut (WSI), 2004)
The notion of flexicurity was introduced in the 1990s to promote a better job security and social security of atypically employed (other than permanent full-time). The given paper suggests an operational definition of flexicurity which implies the corresponding flexicurity index. For analytical purposes two other indices, the Norm-security of 'normally', i.e. permanent full-time, employed and the All-security of all, i.e. both 'normally' and atypically employed, are defined. The indices are derived from qualitative juridical data. For this purpose, employment groups in different countries are ranked with respect to five partial criteria: the eligibility to public pensions, to unemployment insurance, etc. Due to the specificity of criteria, the ranking is generally possible and is not that confusing as the task of numerical evaluation. A dedicated mathematical proposition estimates the error in the index which results from 'ordinal rounding' of the input variables comparing to using the 'exact' variable values. Thus even if the 'exact' (latent) variables are not known then the rank-scaled input is sufficient to approximate the index which otherwise could not be obtained at all. The index is calculated for 16 European countries for the years 1990-2003.
Keywords: J65; J21; J88; J83; C51; J26; C43; 330; Flexicurity; employment security; social security; employment protection legislation; fringe benefits; European Union; statistical indices; Arbeitsverhältnis; Ungeschützte Beschäftigung; Arbeitsmarktflexibilisierung; Soziale Sicherung; Sozialer Indikator; EU-Staaten